MITIGATION OF BULLYING ON STUDENTS IN PESANTREN; FOSTER CARER STRATEGY - Indi Aunullah; Rofiqi Rofiqi; Muhammad Kholil; Samsi Elvia Windari; Naser Ali Abdulghani (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
Islamic boarding schools are a place for students and a place to educate students so they can live independently with the guidance of applied religious teachings. Islamic boarding schools are currently tarnished because of the increasing cases of bullying, but this incident will never reduce the enthusiasm of the caregivers and Islamic boarding school administrators to overcome the problems that occur in Islamic boarding schools. The aim of this research is to determine the strategies of foster carers in dealing with bullying of students in Islamic boarding schools. This research uses a qualitative approach with a case study type of research. The place of this research is at the Nurul Jadid Islamic Boarding School, especially the Az-Zainiyah Region, Village. Karanganyar, District. Paiton, Kab. Probolinggo. The data collection techniques used were observation, interviews and documentation. Meanwhile, data analysis techniques are used by collecting data, reducing data, presenting data, and drawing conclusions and verification. The research results show that several foster carer strategies that can be applied in overcoming bullying against students include: Interpersonal Communication, Modeling, and seminars. Having a foster care strategy implemented can help reduce students from doing as they please which can lead to bullying behavior, and can help Islamic boarding schools, especially the Az-Zainiyah region, to be environmentally friendly and caring. Foster carers play a very important role in overcoming bullying against students, so that bullying behavior does not continue to become a tradition.